2009
DOI: 10.1016/j.molcel.2009.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Sequence-Specific Intramembrane Proteolysis: Identification of a Recognition Motif in Rhomboid Substrates

Abstract: SummaryMembers of the widespread rhomboid family of intramembrane proteases cleave transmembrane domain (TMD) proteins to regulate processes as diverse as EGF receptor signaling, mitochondrial dynamics, and invasion by apicomplexan parasites. However, lack of information about their substrates means that the biological role of most rhomboids remains obscure. Knowledge of how rhomboids recognize their substrates would illuminate their mechanism and might also allow substrate prediction. Previous work has sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
332
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(352 citation statements)
references
References 47 publications
20
332
0
Order By: Relevance
“…4C). N-terminal sequencing of the cleavage products confirmed that the chimeric substrate was cleaved at the same Ala-His bond in detergent solution and in the lipid bilayer (31). We quantified and compared the initial rates of proteolysis and found that, under our assay conditions, the reaction in DMPC vesicles was about twice as fast as that in the detergent NG (Fig.…”
Section: Cocrystallization Of Glpg With a Class-specific Inhibitor-mentioning
confidence: 65%
See 1 more Smart Citation
“…4C). N-terminal sequencing of the cleavage products confirmed that the chimeric substrate was cleaved at the same Ala-His bond in detergent solution and in the lipid bilayer (31). We quantified and compared the initial rates of proteolysis and found that, under our assay conditions, the reaction in DMPC vesicles was about twice as fast as that in the detergent NG (Fig.…”
Section: Cocrystallization Of Glpg With a Class-specific Inhibitor-mentioning
confidence: 65%
“…lacking the TM domain), there is also the concern that they may induce a different type of conformational change in the protease. To examine whether S5 undergoes any major conformational change during the binding and hydrolysis of real protein substrate, we studied the effect of cross-linking S5 to a neighboring helix (S2) on the activity of the protease against a fusion protein containing the TM region of Gurken, a natural substrate of Drosophila rhomboids (31). This approach has been attempted in an earlier study, but the result was not conclusive (22).…”
Section: Cocrystallization Of Glpg With a Class-specific Inhibitor-mentioning
confidence: 99%
“…iRhoms interact with their TM clients, suggesting that they use a vestigial 'exosite' for recognition [19,58]. This feature, harbored within the rhomboid core, has been reported for active rhomboids [88,89] and may dependent on dimerization. For fly iRhom, recognition precedes passing a client into ERAD, whereas for mammalian iRhoms, it directs the client protein's vesicular trafficking.…”
Section: Discussionmentioning
confidence: 95%
“…This enigma was resolved when rhomboids were shown to be serine proteases controlled by a catalytic dyad (Lemberg et al 2005). Rhomboids cleave their substrates within or close to the upper part of the transmembrane domain (Urban et al 2003;Strisovsky et al 2009), but this raises the question of water accessibility for a proteolytic reaction in a membrane environment. This was resolved by high-resolution crystal structures of bacterial rhomboids.…”
Section: Regulation Of Egfr Signaling In Drosophila By Ligand Proteolmentioning
confidence: 99%